RADIKALISME DAN PLURALISME AGAMA : Konflik Antarumat Agama dan Relasi Kekuasaan Industri di Kabupaten Bekasi - Iswadi, Dede; Sabeni, M. (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2010)
Radicalism and religious pluralism are two conflicting paradigms in religious life, but in the political, social, economic and cultural rights, for both are referred to as the Opposition binner in addition, also the two things that are difficult to compromise and separated in religious life. On the one hand, radicalism based on the paradigm of the exclusive negate someone else (the other), rigid, closed, the extremism and militarism are not uncommon; was emphasizes pluralism paradigm based on human values, openness and inclusiveness, fenomema focus of research related to the rejection of religious radicalism in the form of construction of places of worship, especially church, significance of this research are expected to: provide objective information and data-scientific community and the government over the issue of religious radicalism as embodied in the form of denial of the construction of houses of worship in a number of areas in the district of Jakarta. The research was conducted in the district of Jakarta, particularly among civil society organizations (NGOs) Islamic national and local, other stakeholders such as the Christian religious leaders, among industrialists, and government district Bekasi yourself by using methods grottnded Reaserch. Since the first, the public has been taught and lived side by side with non- Muslims, Buddhists and Hindus in particular. Between a religion with people of other religions to respect and appreciate each other Respect the laws and regulations governing the construction of Worship. But ironically, the industry appears to be less instrumented in building inter-religious harmony in the midst of the community